Magnetic-field induced sustainable electrochemical energy harvesting and storage devices: Recent progress, opportunities, and future perspectives. (September 2021) - Roy, Krishnendu; Devi, Pooja; Kumar, Praveen
Abstract: As the search for a superlative alternate to fossil fuels is facing challenges for commercial-scale harvesting and storage, new and novel approaches have been identified to overcome the existing scientific and technological hurdles. Among the various reports, the magnetically induced enhancement has gained a lot of attention due to its efficiency, tunability, affordability, and also its feasibility for large-scale production. However, understanding in this area is yet limited and remains familiar to a limited number of researchers, which needs thoughtful efforts to overcome the existing fundamental and technological barriers. Some recent advanced experiments have revealed fascinating science and technological supremacy which have attracted great attention of the scientific community. Further, it has been predicted that the continuous and systematic futuristic development of this field will allow the magnetic field to be established as an efficient system with minimal energy consumptions for large-scale applications. This review discusses the effect of the magnetic field along with explanation of the mechanism on electrochemistry, related fundamental concepts, green energy generation, and storage applications followed by their future perspectives. Graphical Abstract: ga1 Highlights: Recent advanced experiments of magnetically enhanced electron transfer, spin state-dependent phenomena for electrochemistry. Inclusive discussion on the effect of the magnetic field in the electrochemical energy harvesting and storage devices. Energy Harvesting Devices: Photovoltaics, Water splitting, CO2 reduction, and Fuel Cells. Energy Storage Devices: Supercapacitors and Batteries. Comprehensive summary and future perspectives of the magnetic field induced energy harvesting and storage applications.